Strengthening Financial Working Capital through Fintech Platforms and Product Innovation via Digital Marketing in MSMEs - Arbiya Magfiroh Rohmi; Sriyono; Muhammad Yani (LP2M IAIN Palopo, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in economic development; however, many still face challenges in accessing financial services and optimizing digital technology to strengthen their financial capacity. This study aims to analyze the influence of fintech platforms and product innovation on working capital, as well as the mediating role of digital marketing among MSMEs. The research employs a quantitative explanatory approach using survey data collected from 200 food and beverage MSMEs in Sidoarjo Regency, Indonesia. The sampling technique used is purposive sampling based on specific criteria related to fintech usage and digital marketing activities. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS software. The results show that fintech platforms and product innovation have a positive and significant effect on working capital, while fintech also has a positive and significant influence on digital marketing. Product innovation has a significant but negative effect on digital marketing, and digital marketing shows a significant negative effect on working capital. Furthermore, digital marketing is proven to significantly mediate the relationship between fintech and working capital, but it does not mediate the relationship between product innovation and working capital. These findings indicate that fintech adoption plays a crucial role in strengthening MSMEs’ financial capacity both directly and indirectly through digital marketing activities. The study implies that integrating fintech utilization with digital marketing strategies can support MSME financial sustainability and market expansion. Policymakers and stakeholders are encouraged to enhance digital financial literacy, fintech accessibility, and digital marketing capability among MSMEs to strengthen their competitiveness in the digital economy. Future studies are recommended to include additional variables and broader sectors to further explore the role of digital transformation in MSME performance.